2008
DOI: 10.1159/000162299
|View full text |Cite
|
Sign up to set email alerts
|

The Social Phobia Psychotherapy Research Network

Abstract: This paper presents the Social Phobia Psychotherapy Research Network. The research program encompasses a coordinated group of studies adopting a standard protocol and an agreed-on set of standardized measures for the assessment and treatment of social phobia (SP). In the central project (study A), a multicenter randomized controlled trial, refined models of manualized cognitive-behavioral therapy and manualized short-term psychodynamic psychotherapy are compared in the treatment of SP. A sample of 512 outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Another question is whether the benefit in terms of effectiveness is worth the potential cost differences when evaluated with recently upcoming state-of-the-art cost-effectiveness analyses [e.g. [52,53]]. From these analyses within our study sample, it appeared that the mean direct treatment costs of the 5 treatment modalities were EUR 10,005 (SE 1,134) for long-term outpatient treatment, EUR 16,813 (SE 1,361) for short-term day hospital treatment, EUR 27,648 (SE 2,654) for long-term day hospital treatment, EUR 25,933 (SE 859) for short-term inpatient treatment, and EUR 49,260 (SE 2,435) for long-term inpatient treatment [Soeteman, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Another question is whether the benefit in terms of effectiveness is worth the potential cost differences when evaluated with recently upcoming state-of-the-art cost-effectiveness analyses [e.g. [52,53]]. From these analyses within our study sample, it appeared that the mean direct treatment costs of the 5 treatment modalities were EUR 10,005 (SE 1,134) for long-term outpatient treatment, EUR 16,813 (SE 1,361) for short-term day hospital treatment, EUR 27,648 (SE 2,654) for long-term day hospital treatment, EUR 25,933 (SE 859) for short-term inpatient treatment, and EUR 49,260 (SE 2,435) for long-term inpatient treatment [Soeteman, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, short-term psychodynamic group treatment for generalized social phobia was superior to a credible placebo control [71]. In a large-scale multicenter RCT, the efficacy of PDT and cognitive therapy in the treatment of social phobia was studied [52,72]. Both treatments were significantly superior to the waiting list.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the SOPHO-NET trial in adults [18-20], rates of response and remission based on the LSAS-CA were determined. Following recommendations by Liebowitz et al [23], remission was defined as a score ≤30 on LSAS-CA [29].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding SAD, the RCT by Bögels et al [17] found CBT and PDT equally efficacious in adults. In a large multicenter RCT ( n = 495, Social Phobia Psychotherapy Research Network [SOPHO-NET] trial A1) conducted within SOPHO-NET [18], we found PDT to be efficacious in SAD [19]. In a comparison of CBT and PDT, we found some small differences in favor of CBT at postassessment, but no significant differences in the long term [19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation